Introducing the PRIME DIEP Flap: The Next Evolution in Autologous Breast Reconstruction - McGarry, Kevin M.; Chen, Jenny; Aschen, Seth Z.; Nelson, Jonas A.; Allen, Robert J., Jr. (Journal of Reconstructive Microsurgery Open, 2025)
Following its initial description in 1994, the deep inferior epigastric perforator (DIEP) flap has become the gold standard in autologous breast reconstruction. While sequential modifications have improved patient outcomes, functional donor site morbidity, abdominal bulge, and hernia remain a challenge. Techniques such as robotic surgery show promise in mitigating these issues but are limited by the need for specialized equipment and training.The Paramedian Reflection for Innervated Muscle Enhancement (PRIME) DIEP flap is a novel technique that preserves innervated rectus muscle and minimizes fascial disruption without requiring robotic assistance for flap harvest. Patient selection is based on preoperative imaging, identifying a suitable dominant medial row perforator(s) with a short intramuscular course. A limited fascial incision over the perforator, followed by a paramedian fascial extension, medial reflection of the rectus abdominis, and submuscular pedicle dissection, allows for safe visualization while minimizing abdominal wall morbidity.Between June 2023 and February 2025, 15 patients underwent 18 PRIME DIEP flaps. All flaps survived, with one patient requiring reoperation for hematoma. There were no flap losses, readmissions, or donor site complications, such as bulge or hernia, at 30-day follow-up. About 72.2% of flaps were based on a single perforator, with an average flap weight of 631.7 g.The PRIME DIEP flap represents the next evolution in autologous breast reconstruction by offering a reproducible, muscle- and nerve-sparing technique, enhancing abdominal wall function in suitable patients. This technical modification also allows for the incorporation of the fascial closure in a midline plication, which may improve vascularity of the fascia following DIEP flap harvest. Further prospective studies are underway to evaluate the impact on long-term functional outcomes and further refine patient selection criteria.
Keywords: DIEP flap; PRIME DIEP; abdominal wall morbidity; autologous breast reconstruction